Eco-biology and management of citrus leaf miner: Phyllocnistis citrella ( Stainton) in Meghalaya - Syngkon, Shembha; Thakur, N.S. Azad (Umiam : CPGS, CAU, 2009)
Seasonal incidence of citrus leaf miner (Phyllocnistis citrella) was studied on ten infested citrus plants by recording number of miners on ten infested twigs from each plant, in the citrus orchard during 2008. The incidence of the pest was first noticed in the third week of February (2.67 %) and it reached its peak in the third week of August (31.5%). The pest was not observed from second week of December onwards till second week of February. The biology of P. citrella was carried out under the net house conditions in different months. The duration of various stages of P. citrella was shortest during July 15 to August 15 and longest during November 6 to December 16. The incubation, larval, pupal and total developmental period (egg to adult emergence) ranged from 2-8 days, 4-12 days, and 5-17 days and 11-33 days, respectively. Adult male and female longevity was found to be 3-10 days and 4-12 days, respectively. Fecundity ranged from 27.23 to 47.10 eggs/female, egg hatching from 27.23 to 47.10% and larval mortality from 22.42 to 33.91% in different months. The average sex ratio was found to be 1.37: 1 (female: male). Amongst the abiotic factors, temperature was found to favour the incidence and development of P. citrella. The management with different pesticides along with botanicals revealed that amongst the synthetic insecticides, imidacloprid (0.075 %) was the most effective in reducing larval population and per cent infestation, followed by monochrotophos, spinosad, endosulfan and lamdacyhalothrin in their order of efficacy, whereas amongst the botanicals karanjin (2 %) was found to be the most effective followed by azadirachtin 300 ppm and neem EC, however, prithvi garlic gold was found to be the least effective.
Keywords: Citrus leaf miner; Entomology; Pest control; Phyllocnistis citrella